Hubungan Penyakit Asam Urat dan Rata-Rata Jarak Jalan Kaki terhadap Penyakit Hipertensi yang Diderita Istri di Desa Babakan, Kecamatan Dramaga, Kabupaten Bogor - Putri, Marini; Sukandar, Dadang; Megahandayani, Keni Tyradh (Jurnal Ilmu Gizi dan Dietetik, 2024)
This study aims to analyze the relationship between gout and the average distance walked per day on wives' hypertension in Babakan Village, Dramaga District, Bogor Regency. This research was conducted through a survey with stratified random sampling. Data collection was carried out through interviews using questionnaires. This research was conducted in August-November 2022 in Dramaga District, Bogor Regency. Gout and walking habits are associated with hypertension. Gout (OR 4.17; Cl 95%:1.258-13.847) is a risk for wife’s hypertension. On the other hand, walking (OR 0.999; Cl 95%:0.998-1.000) was a protective factor against wife's hypertension.